Time to first treatment after colonoscopy in patients suffering from colon or rectum cancer in France. Issue 6 (December 2015) - Kudjawu, Yao Cyril; Eilstein, Daniel; Decool, Elsa; De Maria, Florence; Beltzer, Nathalie; Chatellier, Gilles
Highlights: We analyzed data from hospital discharge and long term illness databases. We studied times to treatment after colonoscopy in patients with colon or rectum cancer. Times to treatment were studied according to the patients pathway and to the treatment combination. We studied time to surgery according to the residence of the patients. Abstract: Background: Time to treatment of cancer is becoming a serious political and social issue. A greater understanding of the timeframes involved in cancer care is needed to reduce inequalities in access to care caused by delays. Objective: To describe indicators of time to first treatment after colonoscopy in colon cancer (CC) and rectum cancer (RC) patients in France. Method: Using the international classification of diseases and medical procedures codes, from national hospital discharge and long term illness databases we selected patients newly diagnosed for CC or RC in 2009–2010 who had undergone treatment. Results: We included 15 694 and 6 623 patients for CC and RC, respectively. Median times to surgery in patients with a surgical treatment pathway for CC and RC were 22 (Q1 = 14; Q3 = 34) and 97 (Q1 = 34; Q3 = 141) days, respectively. Median times to chemotherapy for patients with a non-surgical treatment pathway, for CC and RC were 36 (Q1 = 21; Q3 = 59) and 40 (Q1 = 27; Q3 = 59) days, respectively. The median time to radiotherapy in RC patients was 53 (Q1 = 39; Q3 = 78) days.Time to surgery as first treatment in RC patients (46 days) was twice as long as that in CC patients (22 days). Time to treatment was longer in most northern regions and in overseas districts, and shorter in southern regions, for both CC and RC. Conclusion: The findings in this unprecedented study in France will inform decision-making policies on the future implementation of guidelines on timeframes for colorectal cancer treatment access.